«Isine qosıp tigilsin» povestinde qaharman obrazın jasaw sheberligi - Jawlıbaeva, N (SCIENCE and SOCIETY, 2025)
The article discusses the skill of creating an image in the novel "Isine qosip tigilsin" by writer Sh. Seytov. In particular, the psychological aspects of character creation are analyzed in detail.
Keywords: Sh.Seytov; prose; skill; artistry; style; narrative; image; plot; landscape; detail